A CASE STUDY OF LANGUAGE COMPETENCE IN PRIMARY SCHOOL - Nursalim; Indres Novri Yanti; Aisyah Elvina Sari; Nabila Muna Mufidah (Universitas Islam Negeri Mataram, 2025)
Language skills are a fundamental aspect of learning at the elementary school level, including listening, speaking, reading, and writing skills. These four skills are interrelated and are important in supporting students' success in understanding and conveying information effectively. This study aims to analyze the level of language competence of grade V students of SD Negeri 007 Bonai Darussalam because language competence is a key element in language learning that supports students' ability to think, communicate, and socialize effectively. This study uses a quantitative approach with a descriptive method. This study's population is all class V students, totaling 30 people, and the data collection techniques are carried out through tests and performance assessments developed based on curriculum indicators. The data was analyzed using descriptive statistical methods to determine the average score of each aspect of language skills. The results showed that students' language competence in general was in the Sufficient category with an overall average score of 74.8. Reading skills obtained the highest score with an average of 80.5 (Good category), followed by listening skills of 76.4 (Good), 72.3 (Good), and writing 69.2 (Fair). This study concludes that students are superior in receptive skills (listening and reading) to productive skills (speaking and writing). Therefore, it is necessary to strengthen learning strategies oriented towards developing productive skills through contextual, communicative, and collaborative approaches.